2013
DOI: 10.18869/acadpub.3dj.2.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Bond Strength of Fiber-Reinforced Composite (FRC) Posts to Radicular Dentin Using Different Adhesive Cement: an in-vitro study

Abstract: Introduction: Retention of fiber reinforced composite posts depends on the bond strength between post and cement, and cement and root dentin. The aim of this study is to evaluate the bond strength of one type of fiber post to radicular dentin with different adhesive cements. Materials and Methods: Crowns of 44 cariesfree, human premolar were removed 2 mm below the CEJ and the roots were endodontically treated, then prepared for post cementation. The samples were randomly divided into 4 groups, group 1: Breeze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The type of RC also affects retention, as Maryam et al found that the narrow canal held water due to surface tension, making it difficult for the bonding agent to replace it. As a result, even though the RCs were dried using paper points, the bond strength of the etch and rinse technique was lowered due to increased moisture content [27].…”
Section: Materials and Methods Discussionmentioning
confidence: 99%
“…The type of RC also affects retention, as Maryam et al found that the narrow canal held water due to surface tension, making it difficult for the bonding agent to replace it. As a result, even though the RCs were dried using paper points, the bond strength of the etch and rinse technique was lowered due to increased moisture content [27].…”
Section: Materials and Methods Discussionmentioning
confidence: 99%
“…The type of RC also affects retention, as Maryam et al found that the narrow channel held water due to surface tension, making it difficult for the bonding agent to replace it. As a result, even though the RCs were dried using paper points, the bond strength of the etching and rinse technique was lowered due to increased moisture content [22].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported contradicting results when GIC was used as a bonding agent. This may be because of the usage of 40% citric acid and 3% NaOCl before cementation [22]. The reaction of RMGIC results in an enhanced adaptation to the RC, which may favor the friction resistance to dislodgment of the post.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation